1990
DOI: 10.1007/bf01200938
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and biochemical changes during the fermentation of maize (Zea mays) grains formasa production

Abstract: Microorganisms associated with fermentation ofmasa wereLactobacillus plantarum, Pediococcus acidilactici, Lactobacillus fermentum andSaccharomyces cerevisiae. During the fermentation of maize grains, the temperature and moisture increased and the pH decreased. Most amino acids decreased in concentration during fermentation, with glutamic acid being the most abundant amino acid, but he protein content of the 'masa' increased during fermentation. The bacteria played the major role in the fermentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…The pH decrease is in accordance with that reported by Oyeyiola (1990). This author reported that the rate of pH decrease of masa (fermented maize) is significant during the first 6 h of preparation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pH decrease is in accordance with that reported by Oyeyiola (1990). This author reported that the rate of pH decrease of masa (fermented maize) is significant during the first 6 h of preparation.…”
Section: Discussionsupporting
confidence: 93%
“…The yeast population is absent in munkoyo during the first 15 h of preparation. A similar observation has been made for fermented maize (Oyeyiola, 1990). The yeast population count and alcohol content are observed after 24 h of wort incubation in the calabash.…”
Section: Discussionmentioning
confidence: 52%
“…The small number of units of Enterobacteriaceae and other Gram-negative bacteria showed that their growth might have been inhibited due to the presence of lactic acid, resulting in the decrease in the decrease of pH to 4.0 this agrees with Oyeyiola (1990, Chavan 1998) that L. plantarum, was one of the major the major isolates during the production of fermented cereal 'ogi'. The predominance of L. plantarum, L. brevis in this study may be due to secretion of other compounds probably from cowpea which might inhibit the growth of other bacteria and yeasts in the fermenting medium.…”
Section: Resultssupporting
confidence: 73%
“…Among the Pediococcus species we found, P. pentosaceus had previously been identified in kenkey and white maize grains steeped for 24 h for ogi (Halm et al, 1993; Teniola et al, 2005) while P. acidilactici was also found in kenkey and during maize fermentation for masa (Oyeyiola, 1990; Halm et al, 1993; Fowoyo and Ogunbanwo, 2010; Sanni and Adesulu, 2013) and recently, in sorghum ogi (Banwo et al, 2012). Our study is therefore the first report on association of P. acidilactici and P. claussenii with ogi production from maize.…”
Section: Resultsmentioning
confidence: 56%